2010
DOI: 10.1097/brs.0b013e3182023438
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Surgery: Lateral Approach Interbody Fusion

Abstract: Current data corroborates and contributes to the existing body of literature describing XLIF outcomes. Procedures are generally performed with short OR times, minimal EBL, and few complications. Patients recover quickly, requiring minimal hospital stay, although transient hip/thigh pain and/or weakness is common. Long-term outcomes are generally favorable, with maintained improvements in patient-reported pain and function scores as well as radiographic parameters, including high rates of fusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
150
2
8

Year Published

2011
2011
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 277 publications
(167 citation statements)
references
References 64 publications
7
150
2
8
Order By: Relevance
“…However, the determination of absolute prevalence of deficits and their natural history as well as contributing factors remains incomplete and controversial in the literature. Overall, the number of postoperative neurologic events ranges in literature between 0.6 and 33.6% after LLIF [10,11,[13][14][15][16]. In a study by Tohmeh et al [12] 28% of patients experienced a new iliopsoas weakness and 18% claimed of sensory loss at the upper medial thigh although intra-operative real-time monitoring was used to prevent neurologic deficits after LLIF.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the determination of absolute prevalence of deficits and their natural history as well as contributing factors remains incomplete and controversial in the literature. Overall, the number of postoperative neurologic events ranges in literature between 0.6 and 33.6% after LLIF [10,11,[13][14][15][16]. In a study by Tohmeh et al [12] 28% of patients experienced a new iliopsoas weakness and 18% claimed of sensory loss at the upper medial thigh although intra-operative real-time monitoring was used to prevent neurologic deficits after LLIF.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, patient positioning in the proper orientation (hips and knees flexed) could help avoid femoral nerve stretch and allows for more gentle dissection upon retractor employment. All of these factors could reduce the chances of neuropraxia [16]. Although Park et al [6] showed that the lumbar plexus with hip flexion travels more anterior (non-significant) the advantages of a relaxed and therefore easier-to-dissect muscle seem to out weigh the change in position of the nerves.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a series of 84 patients with a mean 15.7 month follow-up, 68 patients demonstrated solid arthrodesis on a computed tomography scan. Peri-and postoperative complications were 2.4% and 6.1%, respectively [9]. Another series of 600 patients and 741 levels reported no wound infections, vascular injuries, or intraoperative visceral injuries, but four cases (0.7%) of transient postoperative neurologic deficit occurred [3].…”
Section: Outcomes and Complicationsmentioning
confidence: 95%
“…The concept of minimally invasive, extreme lateral interbody fusion (XLIF) technique was first reported in early 2000s by Pimenta [1] and has gained widespread acceptance among spine surgeons [2]. It is based on lateral retroperitoneal transpsoas approach and electrophysiological navigation inside the psoas major muscle to avoid damaging the lumbar plexus.…”
Section: Introductionmentioning
confidence: 99%